2010
DOI: 10.1017/s0022112010003733
|View full text |Cite
|
Sign up to set email alerts
|

Decay laws, anisotropy and cyclone–anticyclone asymmetry in decaying rotating turbulence

Abstract: The effect of a background rotation on the decay of homogeneous turbulence produced by a grid is experimentally investigated. Experiments have been performed in a channel mounted in the large-scale 'Coriolis' rotating platform, and measurements have been carried out in the planes normal and parallel to the rotation axis using particle image velocimetry. After a short period of about 0.4 tank rotation where the energy decays as t −6/5 , as in classical isotropic turbulence, the energy follows a shallower decay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(104 citation statements)
references
References 42 publications
11
93
0
Order By: Relevance
“…The breaking of asymmetry between cyclonic and anticyclonic vortices, which has been observed both in experiments [15,25,[28][29][30] and in numerical simulations [20,31,32], is a distinctive feature of rotating turbulent flows. Here we are interested to investigate how this asymmetry is influenced both by the rotation and the confinement of the flow.…”
Section: Cyclonic-anticyclonic Asymmetrymentioning
confidence: 83%
See 1 more Smart Citation
“…The breaking of asymmetry between cyclonic and anticyclonic vortices, which has been observed both in experiments [15,25,[28][29][30] and in numerical simulations [20,31,32], is a distinctive feature of rotating turbulent flows. Here we are interested to investigate how this asymmetry is influenced both by the rotation and the confinement of the flow.…”
Section: Cyclonic-anticyclonic Asymmetrymentioning
confidence: 83%
“…Moisy et al [25] have shown that flow fields originating from grid-generating decaying turbulence remain highly 3D, even at large rotation rates. Vertical velocity was not behaving as a passive scalar and its coupling with the large-scale flow was suggested to trigger shear instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Baroud et al (2003) investigated turbulent water jets in a rotating annulus at Re λ = 360, and found the turbulent flow to be highly intermittent, independent of the Rossby number. Morize, Moisy, and Rabaud performed several experiments of decaying rotating turbulence in large and small facilities (Morize et al, 2005, Morize and Moisy, 2006, Moisy et al, 2010, and described in details some aspects of the coupling between the inertial wave pattern and the decaying turbulent field using high-resolution PIV. Accurate visualisations by means of reflective flakes of the formation and evolution of columnar eddies in rotating turbulence were performed by Davidson et al (2006).…”
Section: Brief Overview Of Previous Studies Of Rotating Turbulencementioning
confidence: 99%
“…Skipping over many insightful contributions presented in the intervening 35 years, we turn to the study by Moisy et al (2010). Technology has moved on, allowing much F ocus luids on F more detailed measurements.…”
Section: Overviewmentioning
confidence: 99%
“…More surprisingly, the vertical correlation of the vertical velocity only grows a little faster than the horizontal correlation of the horizontal velocity, despite the suppression of ∂w/∂z. What Moisy et al (2010) suggest happens to the vertical velocity fluctuations is one of the major surprises.…”
Section: Overviewmentioning
confidence: 99%